Why Do We Only Get Anime Girl Avatars? Collective White Heteronormative Avatar Design in Live Streams. (July 2022) - Brett, Noel
With live streaming rising in popularity, many people stream the creation of 3D avatars However, many of these avatars end up following a similar output: a hyper-feminized anime girl. Why is this? What are the social and technological processes constructing these avatars? To answer these questions, I propose that human (streamer and audience) and non-human (streaming platform and 3D modeling software) participants interact to produce the cultural experience of the live stream, re-producing common heteronormative, cisgendered, and racialized tropes about bodies and desirable avatars. And so, I take as my object of study the interaction that happens when all of these participants merge, forming what I call a white heteronormative assemblage . I argue that this assemblage is collective, relational, and self-reinforcing. Analyzing the relations between human and non-humans participants helps us turn our analytical lens away from media content or streamer motive, and instead toward the restrictive outcomes of such interactions.